كشف الانتحال في الابحاث الطبية باستخدام الأنطولوجيات الطبية - الخطيب باسل; دشاش ميسون; عمر خالد (Latakia University Journal -Engineering Sciences Series, 2017)
يقدم هذا البحث دراسة مرجعية عن الخوارزميات والأنظمة المتوفرة لكشف الانتحال ، ويقوم بتصميم وبناء تطبيق لكشف الانتحال في الأبحاث الطبية بتوظيف الأنطولوجيات الطبية العالمية المتوفرة على الشبكة العنكبوتية . إن مسألة كشف الانتحال في الأبحاث الطبية المكتوبة باللغات الطبيعية هي مسألة معقدة وتتعلق بالمجال الدقيق للابحاث الطبية . يوجد العديد من الخوارزميات المستخدمة لكشف الانتحال في اللغات الطبيعية والتي تقسم بشكل عام إلى صنفين رئيسين هما خوارزميات المقارنة بين الملفات عن طريق بصمات الملفات ،وخوارزميات مقارنة محتوى الملفات والتي تتضمن خوارزميات مقارنة السلاسل النصية وخوارزميات مقارنة البنى الشجرية للملفات . حديثا تم البحث في مجال خوارزميات كشف الانتحال ذات البعد الدلالي فتم تطوير خوارزميات كشف الانتحال الدلالية المعتمدة على تحليل نماذج الاقتباس في الأبحاث العلمية . تمَ في هذا العمل تطوير نظام لكشف الانتحال باستخدام محرك البحث Bing ، حيث تم استخدام خوارزمية تعتمد على استخدام وتوظيف نوعين من الانطولوجيات وهي الأنطولوجيات العامة مثل وورد نت ( WordNet ) والأنطلوجيات الطبية العالمية أشهرها أنطولوجيا الأمراض Diseases ontology التي تحتوي على توصيف الأمراض وخصائصها وتعريفها واشتقاق الأمراض من بعضها. This paper presents a reference study of available algorithms for plagiarism detection and it develops semantic plagiarism detection algorithm for plagiarism detection in medical research papers by employing the Medical Ontologies available on the World Wide Web. The issue of plagiarism detection in medical research written in natural languages is a complex issue and related exact domain of medical research. There are many used algorithms for plagiarism detection in natural language, which are generally divided into two main categories, the first one is comparison algorithms between files by using fingerprints of files, and files content comparison algorithms, which include strings matching algorithms and text and tree matching algorithms. Recently a lot of research in the field of semantic plagiarism detection algorithms and semantic plagiarism detection algorithms were developed basing of citation analysis models in scientific research. In this research a system for plagiarism detection was developed using “Bing” search engine, where tow type of ontologies used in this system, public ontology as wordNet and many standard international ontologies in medical domain as Diseases ontology which contains a descriptions about diseases and definitions of it and the derivation between diseases.